2019
DOI: 10.1002/jcla.22889
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs2188380 and the risk of breast cancer in southwest Chinese population

Abstract: BackgroundPrevious studies have revealed that the single nucleotide polymorphism (SNP) rs2188380 was identified as a novel locus of gout. Interestingly, gout resulting from high serum uric acid (SUA) was also identified to be associated with the risk of breast cancer (BC). We hypothesized that maybe there was a relationship between rs2188380 and the risk of BC. Therefore, our study was conducted to investigate whether this novel gout‐related SNP (rs2188380) was associated with BC risk as well as the clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The high CYP4B1 expression increased the chances of bioactivation of carcinogenic aromatic amines, thereby leading to a high risk of cancer growth [ 15 17 ]. Gene mutations are associated with protein expression levels, and gene polymorphisms may play a role in disease susceptibility by affecting gene expression and/or enzyme activity [ 18 , 19 ]. Previous studies have reported that CYP4B1 polymorphisms are significantly correlated with the risk of various cancers, such as gastric cancer [ 20 ], bladder cancer [ 21 ], and lung cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high CYP4B1 expression increased the chances of bioactivation of carcinogenic aromatic amines, thereby leading to a high risk of cancer growth [ 15 17 ]. Gene mutations are associated with protein expression levels, and gene polymorphisms may play a role in disease susceptibility by affecting gene expression and/or enzyme activity [ 18 , 19 ]. Previous studies have reported that CYP4B1 polymorphisms are significantly correlated with the risk of various cancers, such as gastric cancer [ 20 ], bladder cancer [ 21 ], and lung cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%